1997
DOI: 10.2307/1592212
|View full text |Cite
|
Sign up to set email alerts
|

Status of Salmonella gallinarum-pullorum Infections in Poultry in Zambia

Abstract: Ten outbreaks of Salmonella gallinarum-pullorum infections on poultry farms in Zambia were investigated. Three cases were seen in day-old broiler chickens and were diagnosed by culture as S. gallinarum-pullorum and characterized as pullorum disease because the mortality was only in the first few weeks. Another case was diagnosed by culture from broiler parent stock. Day-old chicks from two of the three cases were supplied by a hatchery. Five cases in 5-to-18-month-old layer chickens were diagnosed by culture a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 2 publications
1
13
0
1
Order By: Relevance
“…In addition, the data from this work strongly suggest that the basic principles of hygiene and cleaning are very important in the prevention of fowl typhoid, possibly more so than the use of any kind of therapy (9).…”
Section: Discussionmentioning
confidence: 80%
“…In addition, the data from this work strongly suggest that the basic principles of hygiene and cleaning are very important in the prevention of fowl typhoid, possibly more so than the use of any kind of therapy (9).…”
Section: Discussionmentioning
confidence: 80%
“…Fowl typhoid is largely under control in countries with highly regulated industries with enclosed housing and relatively good management, but it is still a major problem in Latin America, South America, the Middle East, in parts of Africa and Korea (Silva, 1985;Sato et al ., 1997;Lee et al ., 2003). The most effective means of control is a combination of stringent management procedures and eradication (Calnek et al ., 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, mortality and morbidity rates were also found to be higher in the young budgerigars in the three different flocks. In addition, the mortality rate in budgerigars was observed to be higher compared with the other species, showing that budgerigars are highly susceptible to salmonellosis (Sato et al, 1997;Lee et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…S. Gallinarum infection primarily causes disease in chickens and turkeys of all ages, whilst the disease has also been described in ducks, quail, ring doves, pheasants, peacocks, peafowl and canaries (Berchieri et al, 2001;Shivaprasad & Barrow, 2008). The morbidity and mortality of FT are highly variable in poultry and are influenced by host age, host susceptibility, nutrition, flock management, and virulence of S. Gallinarum (the latter being a major factor affecting the severity of the disease; Sato et al, 1997). Even though the disease has been well documented (Song et al, 2002;Shivaprasad & Barrow, 2008), there is no detailed report about the pathological and immunohistochemical findings of the disease in budgerigars (Melopsittacus undulatus).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation